2021
DOI: 10.1155/2021/7207994
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Effects of Helical Roof on the Performance of Stairmand High Efficiency Cyclone

Abstract: Cost-effectiveness of a standard and a modified Stairmand high-efficiency type cyclone was compared at various inlet gas velocities. The modified design was obtained by replacing the roof of the standard design with a helical roof. Experiments were conducted by both standard and helical roof designs at the same operating conditions. Results showed that helical roof leads to reduced pressure drop in cyclones while having a negative impact on particle collection efficiency. Reductions in pressure drop can reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Geometric Structure. The cyclone separator used in this study is based on the flat-roof (FR) cyclone separator 25 and the spiral-roof (SR) cyclone separator, 18 with a main body diameter of 300 mm, as shown in Figure 1. At the same time, 3D printing technology was used to print the spiral guide vanes according to the model structure size, and tests were conducted in the D300 cyclone separator.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometric Structure. The cyclone separator used in this study is based on the flat-roof (FR) cyclone separator 25 and the spiral-roof (SR) cyclone separator, 18 with a main body diameter of 300 mm, as shown in Figure 1. At the same time, 3D printing technology was used to print the spiral guide vanes according to the model structure size, and tests were conducted in the D300 cyclone separator.…”
Section: Settingmentioning
confidence: 99%
“…The tangential speed of the spiral-roof separator is reduced, and the radial speed is increased, which is not conducive to particle separation. Karadeniz and Demir also conducted experimental studies on flat-roof and spiral-roof separators. It was found that the efficiency of the spiral-roof separator was reduced, but the pressure drop was reduced by more than 30%.…”
Section: Introductionmentioning
confidence: 99%